PENGARUH SOSIALISASI PERPAJAKAN, KESADARAN WAJIB PAJAK, DAN ADANYA SANKSI PAJAK TERHADAP KEPATUHAN PERPAJAKAN BAGI PROSPECTIVE TAXPAYER - Vionita, Vionita; Kristanto, Septian Bayu (Widya Mandala Surabaya Catholic University, 2018)
The aim of this study is to analyze the effect of taxation socialization, taxpayer awareness and the tax sanctions on tax compliance for prospective taxpayers. The prospective taxpayers are defined as future taxpayers who the subjective obligations as taxpayers begin since they are borned. But, since they have no the tax object, they donot have the tax obligation. This study uses students domiciled in Jakarta as pop-ulation. The sampling method used is convenience sampling. The survey method is used to collect data. The data used in this study is 301 questionairs. The results show that the taxation socialization on the tax compliance for prospective taxpayers is significant and positive. But, the taxpayer awareness and tax sanctions have no effect on tax compliance for prospective taxpayers statistically.